2015
DOI: 10.1007/s10792-015-0084-4
|View full text |Cite
|
Sign up to set email alerts
|

3-Year follow-up after Lasik: assessing the risk factors for retreatment

Abstract: The purpose of this study was to evaluate the correlation of important risk factors for LASIK retreatment and the retreatment rate. A retrospective cohort study was conducted. Records of patients who underwent LASIK between January 2011 and January 2012 at the Zambrano-Hellion Medical Center, Tec de Monterrey (México), and posteriorly underwent LASIK retreatment were identified and risk factors to receive retreatment were assessed using relative risk. Main outcomes were retreatment rate, risk factors for retre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Statistically significant improvement in mean CDVA was not reached in this study, but overall, it remained stable from the preoperative visit to the last visit. CDVA stability is important given that femto-LASIK has been associated with loss of Snellen lines in virgin eyes [24, 25] and even seems to occur more frequently in eyes with prior PK [1822]. In this study, 11 eyes (78.6%) either maintained or improved from the preoperative CDVA, and 21.4% of eyes lost 1 or more Snellen lines, which is similar to results reported in other studies (8% to 36%) [1822].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Statistically significant improvement in mean CDVA was not reached in this study, but overall, it remained stable from the preoperative visit to the last visit. CDVA stability is important given that femto-LASIK has been associated with loss of Snellen lines in virgin eyes [24, 25] and even seems to occur more frequently in eyes with prior PK [1822]. In this study, 11 eyes (78.6%) either maintained or improved from the preoperative CDVA, and 21.4% of eyes lost 1 or more Snellen lines, which is similar to results reported in other studies (8% to 36%) [1822].…”
Section: Discussionmentioning
confidence: 99%
“…Femto-LASIK retreatment is not unique to eyes with prior FLEK, as retreatment in post-PK corneas is known to be more common than in corneas that have not undergone any previous operations [19, 20, 23]. Enhancement rates in virgin eyes have been reported to be approximately 2–6% [24, 25, 29–32] and femto-LASIK post-PK studies have reported rates between 39% and 52.6% [19, 20, 23].…”
Section: Discussionmentioning
confidence: 99%
“…where p o (see Eq. (19)) is the relative observed agreement among raters (who are identical as to their accuracy), and p e (see Eq. 22) is the hypothetical probability of chance agreement, using the observed data to calculate the probabilities of each observer randomly seeing each category.…”
Section: Resultsmentioning
confidence: 99%
“…A thorough search of the relevant literature gives a wide variation (1.00%-27.50%) for the percentage of RCS treatments for myopia that require retreatment, with a good estimate for the average to be of the order of 2.5%-3.00%. Table 1 is a representativebut by no means exhaustivelist of 12 studies from around the world of RCS that required retreatment that was conducted during the last decade [15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: How Often Does Rcs For Myopia Require Retreatment?mentioning
confidence: 99%
“…1,2 The incidence of further refractive surgery has been reported to be as low as 0.18% but as high as 9.4%, depending upon length of followup. [3][4][5] Under these circumstances, there are a variety of retreatment options available to refractive surgeons. 6 Several reports have described techniques for re-lifting a previous LASIK flap with repeat excimer laser treatment and consecutive photorefractive keratectomy (PRK).…”
Section: Introductionmentioning
confidence: 99%